SENYAWA ANTIBAKTERI GOLONGAN FLAVONOID DARI BUAH BELIMBING MANIS (Averrhoa carambola Linn.L) - Sukadana, I M. (Jurnal Kimia (Journal of Chemistry), 2012)
Isolation and identification of active antibacterial compounds from star fruit (Averrhoa carambola Linn). has been carried out. As much as 140.56 g of concentrated methanol extract was resulted from 10 kg star fruit that was macerated using methanol. This extract was dissolved into methanol-water (7:3) and then partitioned with n-hexane and chloroform respectively, resulting in concentrated extracts of 0.10 g of n-hexane, 0.07 g of chloroform, and 48.01 g of water. The result of phytochemical test for flavonoid for all of the extracts suggested that water extracts showed most be test intense to the flavonoid. Separation of water extract using column chromatography resulted in FB fractions that was orange as much as 0.2027 g and contains flavonoid. Infra red and UV-vis spectroscopy were employed in order to identify the FB fraction. The result of identification showed that isolate (fraction FB) was cathechin compounds which contained hydroxyl groups at C-3, C-7 and C-4’. It also had functional groups like –OH, C-H aromatic, C-H aliphatic, C=C aromatic, C-O alcohol, and it did not contained C=O carbonyl group. The isolate inhibited E.coli growth at 100 ppm and S. aureus grouth at 500 ppm.
Keywords: Averrhoa carambola Linn ., flavonoid, antibacterial, isolation, identification